Curcuma Longa - A Review (Advancements in Homeopathic Research, 2022)
Curcuma longa Linn (Turmeric) is proven for its anti inflammatory, antioxidant, antimutagenic, antidiabetic, antibacterial, hepatoprotective, expectorant and anticancerous pharmacological activities. Turmeric has been used for its medicinal properties for various indications and through different routes of administration, including topically, orally, and by inhalation. Curcuminoids are components of tumeric, which include mainly curcumin (diferuloyl methane), demethoxy curcumin, and bisdemethoxycurcmin. This drug was introduced into homoeopathy about four decades ago. Later, there have also been additions in the literature based on re-provings and clinical experiences. This drug has organ affinity to mind, head, stomach, abdomen, respiratory and skin, among others.
Keywords: Curcuma longa; active principle curcuminoid; anti inflammatory; anti cancerous activity